A Comparative Study of Standards-Based Curriculum among Public and Private Junior High School Students’ Achievement in Mathematics in Ghana - Suraj Nurideen; Francis Mwinlaanaa; Henry Manmana Kuubar; Abdul-Mumin Al-hasssan; Yarhands Dissou Arthur (International Journal of Mathematics and Mathematics Education, 2026)
Purpose – To compare the effectiveness of Standards-Based Curriculum (SBC) implementation in Ghanaian public versus private junior high schools (JHS). This study compares the effectiveness of SBC implementation in these sectors. To synthesize insights towards improving SBC implementation with an emphasis on equity, teacher empowerment, and infrastructure. Methodology – Qualitative interviews were conducted with six mathematics teachers and five students. Interviews gathered participants' opinions, perceptions, and personal experiences regarding SBC implementation. A small sample of six (6) mathematics teachers and five (5) students from public and private JHS settings.    Findings – Interview results "reflected positively on the effective implementation" of the SBC from the perspective of the participating teachers and students, and their results reflected positively on the effective implementation of the standards-based curriculum. The study identifies "disparities in implementation between public and private JHS" contributing to concerns about "equity in mathematics achievement. Findings point to the need for prioritizing teacher training and equitable resource distribution as key solutions to actionable insights.   Novelty – The primary novelty presented is the explicit comparative focus on SBC implementation effectiveness, specifically between Ghanaian public and private junior high schools (JHS), an identified area of equity concern. The study synthesizes "empirical insights presumably from the interviews with stakeholder perspectives (teachers and students) to understand the implementation gap. Significance – The study is significant for highlighting systemic inequities in SBC implementation, the gap between SBC goals and classroom reality, and the disparity between public and private schools, which directly impacts educational equity in mathematics achievement.